Trefftz functions in FEM, BEM and meshless methods - Kompiš, Vladimír; Štiavnicky, Mário (Computer Assisted Methods in Engineering and Science, 2006)
The paper contains three different multi-domain formulations using Trefftz (T -) displacement approximation/ interpolation, namely the hybrid-displacement FEM, reciprocity based FEM (multi-domain BEM) and the Boundary Meshless Method (BMM) for a single and multi-domain (MD) formulation. All three methods can lead to compatible formulation with the isoparametric FEM, when the displacements along the common boundaries are defined by same interpolation function. All three T-formulations enable to define more complicated elements/subdomains (the T-element can be also a multiply connected region) with integration along the element boundaries, only.